KAJIAN TATA RUANG LUAR ALUN – ALUN KABUPATEN TRENGGALEK - Bayangkara, Andhika; Zefri (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2021)
Townscape is an art to organize a city (Cullen, 1961). This urban structuring technique isapplied to Trenggalek City Square, a small town in the south of East Java province. As an open spaceand city center, Trenggalek City Square must meet the criteria determined by the Minister of PublicWorks regarding public open spaces. In this study, the authors obtained data that Trenggalek CitySquare meets the criteria of the Minister of Public Works regarding public open spaces. In addition,Trenggalek Town Square uses three structuring techniques proposed by Gordon Cullen in his book TheConcise Townscape (1961).